Sistematización del modelo de auto-evaluación de carreras en la Universidad Técnica de Cotopaxi. - Llumiquinga Guanoluisa, Silvia Rebeca (2018)
Nowadays, both public and private institutions try to improve their processes or activities using different technological means, the Technical University of Cotopaxi in the direction of evaluation and quality assurance do not have a computer system and therefore uses traditional mechanisms such as: Excel with formulas, Google drive to storage information, email and interpersonal communication for such self-evaluations having problems to see the evaluations results for academic periods with their history. As a solution, a web application was developed to facilitate the career evaluation process at the Technical University of Cotopaxi, which the user management, management of the evaluation periods, career management, criteria management, both management of qualitatively and qualitatively evaluations and overall results of the evaluations were carried out. The Scrum agile development methodology was used as a framework to develop the software in the shortest time possible, which in turn will allow future modifications to the initial requirements, or even increase new requirements in the development course to ensure the fulfillment of the Career Assessment Committee in the Technical University of Cotopaxi with the final product. The following work tools were considered, the use of the .Net platform, the C # programming language with the IDE Visual Studio because it is oriented to the development of web applications in a fast way, with a modern software architecture such as the Model Vista Controller and for the information storage the use of the Windows Server 2012 database engine was considered. Like other results, the quality software implementation with functionalities according to the self-evaluation process was obtained with the parameters established by the Evaluation Board, Accreditation and Quality Assurance of Higher Education (CEAACES).